Analisis Pengaruh Qowaid Fiqhiyah Dan Qowaid Ushuliyah Dalam Perbedaan Pendapat Fiqh (Kasus Bunga Bank) - Jamaludin, Nur (Zhafir | Journal of Islamic Economics, Finance, and Banking, 2020)
This paper aims to explore the the defferences of fiqh opinion regarding the issue of interest in the case of financing in the bank. The qawaid fiqiyah and qawaid ushuliyah are used in this study to decide the law of interest imposed to the bank. The finding of this study is based the analysis of the qowaid booth fiqiyah and ushuliyah is the law of interest in the bank is unpermissible. The majority of fuqaha give their opinion that the interest imposed in the bank is similar to the riba nashi’ah